2020
DOI: 10.1002/mar.21355
|View full text |Cite
|
Sign up to set email alerts
|

How product aesthetics cues efficacy beliefs of product performance

Abstract: Aesthetics of package design is an important consideration when consumers make purchase decisions. We argue that this is particularly the case for purchase decision of products in the beauty category. This paper advances current understanding of the role of packaging in product purchase behavior by identifying heuristic cues exhibited in packaging (i.e., that beautiful packaging is more effective at making the consumer more beautiful). Across a pilot field study and four lab studies, we demonstrate that packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Research has yet to examine how native advertising, including social media influencer marketing, affects product efficacy perceptions. Prior research found that factors such as price (Shiv et al , 2005), information about the manufacturer’s profits (Posavac et al , 2010), “green” characteristics (Pancer et al , 2017), and the attractiveness of packaging (Sundar et al , 2013) can all influence consumer perceptions of the product’s performance. In the context of influencer marketing, the consumer is presented with very limited information about the product in the post.…”
Section: Main Study: the Role Of Persuasion Knowledgementioning
confidence: 99%
“…Research has yet to examine how native advertising, including social media influencer marketing, affects product efficacy perceptions. Prior research found that factors such as price (Shiv et al , 2005), information about the manufacturer’s profits (Posavac et al , 2010), “green” characteristics (Pancer et al , 2017), and the attractiveness of packaging (Sundar et al , 2013) can all influence consumer perceptions of the product’s performance. In the context of influencer marketing, the consumer is presented with very limited information about the product in the post.…”
Section: Main Study: the Role Of Persuasion Knowledgementioning
confidence: 99%
“…Importantly, other aesthetic features can also convey these attributes (e.g., complexity can convey quality; Spence, 2018) and symmetry and curvature can convey different attributes (e.g., asymmetry can convey excitement; Bajaj & Bond, 2018). Hence, different aesthetic features may also convey brand premiumness, and the association between aesthetic features and different attributes may be used to convey other brand meanings (Sundar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…People are also influenced by this stereotype when evaluating non-human objects. For instance, people associate more beautiful products, packaging, and web pages with better performance (25)(26)(27). The trust bias in favor of more beautiful graphs found here may be another manifestation of the beauty-is-good stereotype.…”
Section: Discussionmentioning
confidence: 64%